2021
DOI: 10.1093/braincomms/fcab141
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis transcriptomics reveals immunological effects of low-dose interleukin-2

Abstract: Amyotrophic lateral sclerosis is a fatal neurodegenerative disease causing upper and lower motor neuron loss and currently no effective disease-modifying treatment is available. A pathological feature of this disease is neuroinflammation, a mechanism which involves both CNS-resident and peripheral immune system cells. Regulatory T-cells are immune-suppressive agents known to be dramatically and progressively decreased in patients with ALS. Low-dose interleukin-2 promotes regulatory T-cell expansion and was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…It was also observed that pretreatment expression levels of two genes correlated with the magnitude of drug responsiveness, allowing the development of a two-biomarker-based regression model to predict the T reg cell response to low-dose IL-2. These findings and the application of this embedded experimental medicine approach could be particularly relevant for future application of precision medicine approaches in ALS clinical trial design 198 .…”
Section: Als Drug Pipelinementioning
confidence: 90%
See 3 more Smart Citations
“…It was also observed that pretreatment expression levels of two genes correlated with the magnitude of drug responsiveness, allowing the development of a two-biomarker-based regression model to predict the T reg cell response to low-dose IL-2. These findings and the application of this embedded experimental medicine approach could be particularly relevant for future application of precision medicine approaches in ALS clinical trial design 198 .…”
Section: Als Drug Pipelinementioning
confidence: 90%
“…The trial met its primary end point, with both doses of aldesleukin resulting in a significant, dose-dependent, increase in T reg cell numbers, compared with placebo. This increase was accompanied by enhancement of T reg cell suppressive function, suggesting an improved ability to control the inflammatory mechanisms that contribute to neuronal injury in ALS 198 . There was also a significant, dose-dependent drop in CCL2 (MCP-1) levels, an inflammatory biomarker which is frequently elevated in patients with ALS 197 .…”
Section: Als Drug Pipelinementioning
confidence: 94%
See 2 more Smart Citations
“…Therapies such as low-dose IL-2 or IL-2/anti-IL-2 antibody complexes have been advanced in the clinic to preferentially expand Treg populations as a treatment for chronic inflammatory autoimmune diseases [ 43 ]. Some neuroprotective effects of low-dose IL-2 treatment have been found in AD mice [ 44 ] and in amyotrophic lateral sclerosis (ALS) patients [ 45 ]. Nevertheless, no study thus far has investigated the effects of low-dose IL-2 in PD or pre-clinical PD models.…”
Section: Introductionmentioning
confidence: 99%